Enhancing Consumer Protection in Electronic Commerce Transactions - Widijowati, Dijan (LifeSciFi, 2023)
Consumer protection in electronic commerce transactions is a critical aspect of fostering trust and ensuring the safety of consumers in the digital marketplace. The rapid growth of e-commerce in Indonesia has presented new challenges in safeguarding consumer rights and interests. This paper examines the existing legal framework for consumer protection in electronic transactions in Indonesia and highlights the need for effective measures to address risks related to data security, privacy, fraud, and consumer trust. The study utilizes a comprehensive methodology combining normative juridical and empirical juridical approaches to analyze relevant legal texts and secondary data sources. The research emphasizes the importance of upholding consumer rights, promoting fair business practices, and providing avenues for resolving disputes in order to nurture trust, responsibility, and fair commerce practices in the online marketplace.